1999
DOI: 10.1063/1.369399
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index changes of Pd-coated magnesium lanthanide switchable mirrors upon hydrogen insertion

Abstract: The optical effect upon insertion of hydrogen into Pd-coated magnesium lanthanide switchable mirrors is investigated in terms of the changes of their complex refractive indices. A significant change in the optical constants of LnMg layers is seen between the as-deposited state and the dehydrided state after one cycle. Furthermore, the optical effect of switching the Pd cap layer to a PdH cap layer was determined. It is shown that the Pd layer mainly limits the visible transmittance of the hydrided stack to abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 5 publications
1
66
1
Order By: Relevance
“…For this we used the SiO 2 dielectric permittivity given by the Smeiller equation with the Schott industry coefficient as in [12]. For Pd and Pd hydride the experimental dielectric permittivity as obtained by von Rottkay [24] was used. The experimental data of the Pd hydride dielectric permittivity (obtained at 10 5 Pa hydrogen pressure) gives satifiying results compared to the experimental sensor response reported in 4% H 2 in Ar at room condition [12].…”
Section: Simulation Modelmentioning
confidence: 99%
“…For this we used the SiO 2 dielectric permittivity given by the Smeiller equation with the Schott industry coefficient as in [12]. For Pd and Pd hydride the experimental dielectric permittivity as obtained by von Rottkay [24] was used. The experimental data of the Pd hydride dielectric permittivity (obtained at 10 5 Pa hydrogen pressure) gives satifiying results compared to the experimental sensor response reported in 4% H 2 in Ar at room condition [12].…”
Section: Simulation Modelmentioning
confidence: 99%
“…In the transparent states, there is some contribution to the reflectance from the Pd layer, which remains metallic but is somewhat more transparent when loaded with hydrogen. 11 Co-Mg hydride films were strongly absorbing below 500 nm, due in part to their higher reflectance in this region. The maximum transmittance depended upon the thicknesses of both the mixed metal film and the Pd overlayer, as well as on the atomic ratio of transition metal (T) to Mg. Cosputtering from offset sources produced films with position-dependent T:Mg atomic ratios ranging from about 1:1 to 1:10.…”
mentioning
confidence: 99%
“…The results from the models in general do not exactly describe the measured behavior of the films tested; however, the general trends are described and employed to direct the sensor design. 17, 18 These simulations indicated that significant variations between pure Pd and PdH x should be expected in the 200-400 nm range, which enables the detection of H 2 . Calculations were done with 600 μm fiber with a numerical aperture of NA=0.22 and various thicknesses of PdH x .…”
Section: Modeling Resultsmentioning
confidence: 99%